2016
DOI: 10.1136/bmjopen-2016-011344
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of electronic cigarette use in current and ever users among college students in France: a cross–sectional study

Abstract: ObjectiveThere is sparse information on electronic cigarette use and health behaviours among college student populations. Our objectives were to identify the patterns of electronic cigarette use in current and ever users among college students in France.DesignCross-sectional study.SettingsA multicentre cross-sectional study was conducted on two major campuses in France. Students filled in an anonymous questionnaire on their use of electronic cigarettes and on targeted behaviours such as smoking, alcohol consum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
50
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(66 citation statements)
references
References 52 publications
7
50
2
Order By: Relevance
“…Users also report using ENDS because they are less expensive than cigarettes, 145,194,332,337,338,341,350,353,358,372,389,395,455,456,459,472,502 for relapse prevention, 194,353,372 out of curiosity, 341,347,350,358,421,422,432,434,441,444,456,461,476 because they are accessible and convenient, 341,366,387,477 for social reasons, 341,347,363,387,434,444,461,502,504 and because they taste 337,358,426,472,477,496 or smell better than cigarettes. 341,353,389,459,461 Flavors are viewed as an attractive characteristic of ENDS, 345,433 and are a cited reason for vaping.…”
Section: Evidence Synthesismentioning
confidence: 99%
See 3 more Smart Citations
“…Users also report using ENDS because they are less expensive than cigarettes, 145,194,332,337,338,341,350,353,358,372,389,395,455,456,459,472,502 for relapse prevention, 194,353,372 out of curiosity, 341,347,350,358,421,422,432,434,441,444,456,461,476 because they are accessible and convenient, 341,366,387,477 for social reasons, 341,347,363,387,434,444,461,502,504 and because they taste 337,358,426,472,477,496 or smell better than cigarettes. 341,353,389,459,461 Flavors are viewed as an attractive characteristic of ENDS, 345,433 and are a cited reason for vaping.…”
Section: Evidence Synthesismentioning
confidence: 99%
“…Two hundred and fifty articles 153,192194,197,203,239,265,271,304,323326,329,332,333,335339,341344,346,348,350,351,353362,365,367369,372,374376,378381,384,388,390,393396,404406,408,414416,418,420422,425,426,432,434,436,440,441,444450,453456,459462,465,468,472,475,476,478,488,489,491,494,496498,500,502,504,506646 have been published on vaping patterns.…”
Section: Evidence Synthesismentioning
confidence: 99%
See 2 more Smart Citations
“…Surveys in the United States (Arrazola et al, 2015; McCarthy, 2015), New Zealand (White et al, 2015), Korea (Lee et al, 2014), France (Tavolacci et al, 2016), and Poland (Goniewicz et al, 2014) have reported high rates of e-cigarette use among adolescents and young adults. For example, a nationally representative survey in the United States found that e-cigarettes were the most commonly used tobacco product among high school students in 2014, and current (past 30 days) use of e-cigarettes increased approximately nine-fold from 2011 to 2014 among high school students (1.5% in 2011; 13.4% in 2014) and tripled among middle school students (1.1% in 2011; 3.9% in 2014) (Arrazola et al, 2015; McCarthy, 2015; Singh et al, 2016).…”
Section: Discussionmentioning
confidence: 99%